Compra de livros por impulso no social commerce - Berlanga, Luciana da Silva (2023)
This research aims to search for evidence that helps in the comprehension of how social networks influence, motivate and enable the impulsive purchase of books, by understanding the process of decision to buy and elements of this practice, sayings and dos of this behaviour. Therefore, qualitative research was made, by using elements of netnography, in an exploratory character with interviews. As a result, we observed that although social networks are relevant in the generation of purchase traffic, they do not carry enough credibility to generate in themselves all the journey of purchase through the checkout. Although the practices are individualised concerning the consumption of books, they are common in the process of online purchase. The discoveries offered opportunity perspectives to create a digital hub with book related content, where the managers, authors, editors, and other stakeholders will be able to benefit from the expanding promotion of the category.